Inventarisasi Jenis-Jenis Jagung Lokal di Pulau Kadatua Kabupaten Buton Selatan - Taslim Taslim; Agus Slamet; Jumiati Jumiati (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2021)
South Buton especially on Kadatua Island has several types of local corn which are used as staple foods such as kambuse, kapusu, kagili and kambewe. The aim of this study are to determine the types of local corn in Kadatua Island and determine the agronomic and morphological character. This research is classified as descriptive research. Methods was conducted in two stages, namely exploration by collecting local types of corn found on Kadatua Island and characterizing both morphologically and agronomically. Observations observed include; plant height, stem diameter, number of leaves, measurement of leaf length and width, flowering age, number of cob, cob length, ear diameter, harvest age, number of seeds per row, seed weight and type of seeds. The subject in this study was local corn. Measurements were analyzed using qualitative descriptive analysis. The results showed that there were five types of local corn found and scattered on Kadatua Island including kapute (white), kangkuni (yellow), ragi (white pulut), waumbo (black) and kadea (red). The five types of local maize found display diverse morphological and agronomic characters.